Re-Insemination of Egg Laying Queen Honey Bees - Gąbka Jakub; Gąbka Joanna; Zajdel Barbara (Journal of Apicultural Science)
Instrumental insemination of queen bees that have started laying eggs is used extremely rarely. It is one of the methods for obtaining diploid drones, but it is believed that the queen must stop laying eggs for at least five days before insemination, e.g. by placing her in a mesh cage in her colony, in order to deactivate the ovaries. According to unpublished information, re-insemination of queens with active ovaries causes their death. The aim of this work was to verify this information. The results of our experiments show that re-insemination does not affect the survivability of queens with active ovaries and can be performed without prior interruption of egg laying.